Preparation of Expandable Graphite and Its Catalysis Performance for the Synthesis of Isoamyl Acetate - PANG, XIU-YAN; LIU, JIN-HUAN (Asian Journal of Chemistry, 2010)
Five kinds of expandable graphite with different expanded volume and different intercalation compounds are produced. In order to testify the intercalation reaction in graphite, XRD analysis of natural graphite and expandable graphite are carried out. Its catalysis performance for the synthesis of isoamyl acetate is studied. The influence of molar ratio of isoamyl alcohol to acetic acid, amount of catalyst, reaction time, initial intercalation reagents of graphite on the yield of isoamyl acetate is examined in detail. The reusing capability of catalyst is also studied. We get the suitable conditions of the esterification as follows when tetrabutyltitanate is used as intercalation reagent of graphite: molar ratio of isoamyl alcohol to acetic acid equals to 1.5:1.0, mass of catalyst equals to 7.5 % of the total mass of reactants, reaction time is 2.5 h and temperature keeps at boiling point. The esterification rate of 87.9 % can be achieved. Expandable graphite prepared with different intercalation reagents has different catalytic activity, the one with tetrabutyltitanate as intercalation reagent has better catalysis activity for this esterification reaction, and its reuse rates are: 87.9 % for the first time, 63.8 % for the second time and 40.2 % for the third time. Results testify the expandable graphite has higher catalytic activity, short reaction time, easily being separated.